DEVELOPMENT AND IMPLEMENTATION INNOVATIVE MANAGEMENT ENTERPRISE DEVELOPMENT: THE SCIENTIFIC AND METHODOLOGICAL ASPECT - Davydova, Oksana (Social Economics, 2018)
The article considers methodological aspects the formation and implementation innovative management enterprise development in modern market conditions. The parameters on which the development effective management decisions in the enterprise depend. The author has developed the process shaping the effect innovation. A hierarchical system of the influence innovation on the management enterprise development is proposed. The requirements to which the system innovative management enterprise development should correspond are defined. The factors influencing the construction organizational structures innovative management enterprise development are determined. Methodological aspects the formation and implementation innovative enterprise development management have been developed that will provide an opportunity for enterprise management to formulate and implement a system innovative enterprise development management that includes components and principles the innovation management process. These aspects also include the assessment, testing and forecasting innovations in the management system based on epistemological roots and the main directions innovation. Problems innovative management enterprise development are singled out.